2015
DOI: 10.5539/cco.v4n2p24
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor Axis, Adipokines, Physical Activity, and Obesity in Relation to Breast Cancer Incidence and Recurrence

Abstract: BackgroundObesity, a risk factor for the development of postmenopausal breast cancer and certain other cancer types, has also been associated with poorer response to cancer therapy and cancer recurrence. The insulin-like growth factor (IGF) axis also influences cancer risk.MethodsIn this commentary, we consider the literature on IGF and its binding proteins and the risk of breast cancer, along with effects of obesity, adipokines, and insulin resistance on breast cancer, and the potential for lifestyle interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…Evidence from epidemiologic studies indicates that high levels of physical activity reduce breast cancer risk in women. The possible biological mechanisms include the influences of physical activity on body composition, insulin resistance, and circulating levels of sex steroid hormones (17). Eating non-starchy vegetables may also lower the risk of some breast cancers.…”
Section: Modifiable Risk Factors For Breast Cancermentioning
confidence: 99%
“…Evidence from epidemiologic studies indicates that high levels of physical activity reduce breast cancer risk in women. The possible biological mechanisms include the influences of physical activity on body composition, insulin resistance, and circulating levels of sex steroid hormones (17). Eating non-starchy vegetables may also lower the risk of some breast cancers.…”
Section: Modifiable Risk Factors For Breast Cancermentioning
confidence: 99%
“…Evidence from epidemiologic studies indicates that high levels of physical activity reduce breast cancer risk in women (8). The possible biological mechanisms include the influences of physical activity on body composition, insulin resistance and circulating levels of sex steroid hormones (9).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, there were correlations between the intensity of ER and PR IHC staining and the Oncotype ER, PR, and HER2 (according to RT-PCR results, < 0.0001 for all variables). Median ODX RS was 17 (range 0-88) and 50.4%, 38.4%, and 11.2% of the patients had low (0-17), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high (≄31) RS, respectively. (Figure 1) and more intense ER staining (mean 2.59 ± 0.4 versus 2.46 ± 0.58, = 0.032).…”
Section: Patients and Tumor Characteristicsmentioning
confidence: 99%
“…As hyperinsulinemia and insulin-like growth factors were reported to have mitogenic effect on breast cells [17,18], metformin may favorably affect patients with breast cancer. Many in vitro and in vivo studies found that metformin inhibits cancer cell growth, reduces the risk of developing solid tumors, and improves cancer outcome, including breast cancer [11,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%